2017
DOI: 10.1109/tdsc.2017.2681672
|View full text |Cite
|
Sign up to set email alerts
|

Social fingerprinting: detection of spambot groups through DNA-inspired behavioral modeling

Abstract: Spambot detection in online social networks is a long-lasting challenge involving the study and design of detection techniques capable of efficiently identifying ever-evolving spammers. Recently, a new wave of social spambots has emerged, with advanced human-like characteristics that allow them to go undetected even by current state-of-the-art algorithms. In this paper, we show that efficient spambots detection can be achieved via an in-depth analysis of their collective behaviors exploiting the digital DNA te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 47 publications
0
105
0
Order By: Relevance
“…GroupFound achieved a detection rate of 86:27% with a false positive rate of 8:54%. Cresci et al (2018a) observed that it is not enough to merely depend on the history of previous behaviour records to detect new generations of spam bots. Instead, we need to investigate collective behaviors of users' groups to determine whether these account are bots or not.…”
Section: Other Emerging Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…GroupFound achieved a detection rate of 86:27% with a false positive rate of 8:54%. Cresci et al (2018a) observed that it is not enough to merely depend on the history of previous behaviour records to detect new generations of spam bots. Instead, we need to investigate collective behaviors of users' groups to determine whether these account are bots or not.…”
Section: Other Emerging Approachesmentioning
confidence: 99%
“…Interestingly, the very low recall of Yang et al (2013) can be seen as an evidence of a new generation of social bots that are hard to detect when they are considered individually even using current state-of-the-art algorithms. Cresci et al (2018a) approach is flexible in terms of not focusing on specific characteristics. Moreover, it reduces the cost for data gathering by not considering the properties of the social graph.…”
Section: Other Emerging Approachesmentioning
confidence: 99%
“…R1 Show similarities among accounts. This requirement is essential for enabling users to explore different characteristics to cluster the accounts based on [4,10,11].…”
Section: Design Requirementsmentioning
confidence: 99%
“…The system should enable users to highlight and cluster accounts interactively. This interactive clustering is essential to reveal potential group-based spamming activities [10,11].…”
Section: Design Requirementsmentioning
confidence: 99%
“…In other words, users form connections with the elements as they interact in the network, e.g.,through communication with other users. Researchers in this category use data and machine-learning methods to find users that do not conform to certain rules; such techniques usually compare the user activities to a predefined set of activities [1], [11], [23], [8]. In most cases, history-based algorithms need to have a set of predefined standards that describe legitimate users, hence ensuring that the systems adopt the strategy of finding Sybil profiles.…”
Section: B User Behavior-based Mechanismmentioning
confidence: 99%